Women empowerment in rural areas through village relocation programme: a case study in Perumahan Nelayan Muafakat, Kedah - Ahmad, Nabila; Hammad Ahmad Khan, Hafizah; Jamaludin, Husna; Mohd Ramli, Irlisuhayu (2019)
Women are the asset of a country because they play indispensible role in the economic development. Verily, empowerment of women will be able to uplift their livelihood by accelerating their living standards, income, and well-being, particularly in rural areas. The involvement and engagement of rural women in economic and political aspects are vital to go hand in hand with men in decision making, delivering critical idea, and linking in multi-dimensional sectors. By participating in all spheres of life, it could facilitate them to escape from the rural poverty that they are facing now.